La cultura giuridica a Genova negli anni della formazione di Giuseppe Cappi: il paradigma scientifico-universitario - Bracciale, Roberta (Il diritto ecclesiastico, 2024)
Legal culture in Genoa during the formative years of Giuseppe Cappi : the scientific academic paradigm · At the end of the 19th century, the so-called scientific academic paradigm profoundly shaped and transformed Italian legal culture. The causes and outcomes of this change have been investigated by historiography, yet there are still many jurists of the period who deserve greater attention. On these bases, the aim of this article is to reflect on Genoese academic culture through its protagonists, known and lesser-known, with specific reference to the Giolittian age.